Kontekstualisasi Maqaashidu Al-Syariah terhadap Penerapan Hak Ex Officio Hakim - Rusdaya Basri; Rukiah Rukiah (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2020)
This study examines the perspective of judges in applying their ex officio rights to the protection of the rights of children and wives on divorce cases at Religious Court Pinrang. This research assessed with descriptive qualitative approach using observation and depth-interview to the judges. The result shows that the judges absolutely apply their ex officio to the issue of Mut’ah. There are cross-opinion for the issue of iddah alimony for women in post-divorce, some apply and some do not. While for the issue of hadanah or child rearing, madhiyah property, and common property, the judges agreed that those issues are not include in the judges’ ex officio rights. However, it still must be prosecuted to find out the clear real case.